Use of credit card and compulsive buying - Yurtseven, Gülten (Journal of Dependence, 2014)
As a modern payment system, the usage of credit card increased considerably between the end of the 20th and the beginning of the 21th century. Nowadays, credit cards as important financial service used for both as a source of credit and as a means of payment. For many people credit cards are practical way of purchasing goods and services and “buy now, pay later” psychology has become lifestyle of consumers. People prefer to use credit card more than cash as a payment instrument. While usage of credit card provides benefits to the consumer, there are some negative consequences such as leading compulsive buying. Compulsive buying can be defined as irresistible purchasing needs that individuals hold by causinguncontrolled buyingbehavior (endangering physical and mental health, work and economical stability). Compulsive buying may have serious consequences for the customers, their surroundings and society as well. In this paper, the relationship between compulsive buying and credit card usage has been examined. And also the other factors affecting compulsive buying has been investigated.
Keywords: Credit card usage; compulsive behavior; consumer behavior; consumer problems; social behavior disorder